O Colégio Estadual Mário de Andrade de Francisco Beltrão: da fundação à consolidação na formação secundária entre 1964 e 1982 - Severgnini, Alisson Fernando (2020)
This research is linked to the Society, Knowledge and Education Research Line of the Postgraduate Program in Education, at the State University of Western Paraná, and focused on the History of the State School Mário de Andrade (CEMA) by Francisco Beltrão, from its foundation to consolidation as a secondary education institution between 1964 and 1982. The problem / object of research was to analyze what were the motivations for the Implantation of secondary education in Francisco Beltrão. How did the institution create, function and organize? How did the College deal with the laws of the time and the Civicmilitary regime that occurred in the midst of its activities? What courses did you offer? What partnerships have you entered into? What is its impact on the region's economic and social development? Our objective, therefore, was to understand /analyze the history of CEMA in this trajectory, elucidating the issues raised. The research was developed from a dialectical perspective, exploring bibliographic, documentary and oral sources. Interviews with ex-teachers and ex-directors, linked to bibliographic and documentary sources, revealed how, in practice, the institution's organization process took place, partnerships with other school institutions, how the College organized its courses, its resumes, the number of enrollments received, etc. From the analysis of the data, we concluded that CEMA was extremely important for the educational development of Francisco Beltrão, having been a reference in secondary education, both junior and high school. CEMA was, for many years, the only public institution to offer secondary education, in general and technical-professional education modalities. Many CEMA students found, in their portfolios, the path to higher education and the job market.